Balancing and Its Application in Judgment 11-18-CN/19 Regarding "Equal Marriage" in Ecuador - Avalos Barreno, Iván Rodrigo (Ius Humani. Jornal do direito, 2021)
In 2019 the Constitutional Court of Ecuador issued sentence 11-18-CN/19. In this resolution it was affirmed that article 67 of the Constitution-which established that marriage is the union between a man and a woman-was unconstitutional, thus granting the possibility for same-sex people to marry. For this, the Judge Ramiro Ãvila Santamaría, among other arguments, used balancing. The essential part of balancing is the weight formula. However, this was not use in that sentence. Through this argumentative method, it was concluded that the principle of equality prevails over other general principles of law. This paper analyzes the weight formula, applying it in the way that, in my opinion, the Constitutional Court should have done in the " egalitarian marriage" judgment. For this, the analytical-synthetic method is used, breaking down the argumentation made by Judge Ãvila into fragments. The first section deals with the elements of the weight formula. Then the balancing exercise carried out in the sentence is exposed, followed by a demonstration of the argumentative errors committed, highlighting the mistake in choosing the principles in conflict. Finally, a new balancing exercise is presented, confronting the principles that should have been taken to the balance. The paper concludes mainly that the Constitutional Court erroneously applied balancing in the " egalitarian marriage" judgment.